Lifetime of patients and prognostic value of manifestations and complications of liver cirrhosis - G. K. Mirodzhov; S. A. Avezov; N. S. Tukhtayeva; A. Bakhtibekov; M. M. Giyasov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Studying of liver cirrhosis (LC) prevalence in Tajikistan, survival rates, lifetimes and principal causes of death of patients, and evaluation of prognostic value of manifestations and complications of LC.Material and methods. 1374 patients of the LC were investigated. Main etiological factors of development of disease were: hepatitis virus B, hepatitis virus C, alcohol. Results. The incidence of viral LC in Tajikistan does not differ from that in Russia and some western countries and makes 2,32 per 10 000 of adult populations. Alcohol-induced LC and primary biliary cirrhosis are over 10 and 5 times less frequent respectively. Lifetime and 3-year survival rate of patients depend on a phase of cirrhotic process compensation. The highest 3-years survival rate of patients from the moment of establishment of the diagnosis was 79% at class A LC vs 28% at class C LC. At 89% of patients the cause of death has been directly related to complications of cirrhosis. Hepatic encephalopathy and bleeding serve as certain criteria of survival rate prognosis of LC patients. Hepatorenal syndrome, bacterial peritonitis and portal vein thrombosis are independent risk factors of lethal outcomes.Conclusions. Prognosis of survival is most unfavorable at hepatic encephalopathy in comparison to other complications of the LC. Presence more than one complication increases probability of death of patients more than 2,5 times. The relative risk of death is higher at patients with class B and C in comparison to class A.